Defining Asia capabilities for Australia's public service - Bice, Sara; Merriam, Angela (2016)
Twenty-three years ago, questions posed in this journal asked whether and how the Australian public service was prepared to engage effectively in Asia. More recent meta-analyses of public policy scholarship suggest that Western policy scholars and administrators continue to pay limited attention to Asian policymaking, despite the rise of Asia in the 21st century. This article contributes a research-derived Asia capabilities framework for Australia's public service, distilled from a qualitative study with public administration leaders at Commonwealth, state, and local government levels. It taps scholarly literature in 'cultural intelligence', global leadership competencies, and training to provide a robust conceptual underpinning for the framework. The framework defines the knowledge, skills, capabilities, and experiences vital for Australia's public service to engage effectively with the region in a rapidly changing policy environment. - Reproduced.
Keywords: Public administration - Australia; Public administration